Exploring the Enjoyment of Vocabulary Learning through Augmented Reality: Learners Points of View - marifah, shovi zaidatul (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
This study explores students' satisfaction with augmented reality (AR) technology for vocabulary acquisition, focusing on its impact on learner engagement and motivation, as well as the challenges students face. A qualitative approach was employed with five high school students who had experience using AR for vocabulary learning. Data collection involved observations and structured interviews to capture their interactions, perceptions, and satisfaction with AR. The findings reveal that AR enhances engagement and motivation by providing an interactive, immersive, and enjoyable learning experience. Students described AR as gamified and multisensory, which increased their involvement and made learning more appealing. Visualizing vocabulary in real-world contexts improved understanding and sustained interest, while a sense of achievement from progress further boosted motivation. However, challenges included device incompatibility, unstable internet connectivity, and difficulties navigating AR applications due to a steep learning curve and inadequate training. These barriers occasionally hindered effective use and reduced learning efficiency. In conclusion, AR technology shows promise in transforming vocabulary learning through enhanced engagement and motivation. Addressing technical and training-related challenges is critical for optimizing its use in education, offering valuable insights for future implementation.